A concorrência entre a produção de etanol e a produção de alimentos no estado do Rio Grande do Sul - Barbosa, Alessandra da Silva (Universidade do Vale do Rio dos Sinos, 2011)
The Brazilian government incentive programs in biofuels, renewable energy alternatives to petroleum substitutes like ethanol, has raised several issues regarding the effects that this production can generate in the long run, especially in relation to land, since they are used crops such as sugar cane for the production of the fuel and this could jeopardize the food security of the population. The present study aims to determine what is the relationship of competition for land that exists between the production of cane sugar, for the generation of ethanol, and food production in the state of Rio Grande do Sul The methodology used was structural method differential shift-share. Data were collected from the Agricultural Census of 1996 and 2006, the analysis was performed by COREDES and agricultural products chosen for the study were: rice, oats, peanuts, sugar cane, beans, cassava, corn, soybeans and tomatoes. Based on these data, one can say that during the period analyzed the production of cane sugar for the generation of ethanol does not compete with food production in the state of Rio Grande do Sul
Keywords: Etanol; Cana-de-açúcar; Alimentos; Ethanol; Cane sugar; Food; ACCNPQ::Ciências Sociais Aplicadas::Economia